Comparison of Oxcarbazepine Versus Carbamazepine in the Management of Trigeminal Neuralgia in Patients Presenting in the Outpatient Department of Neurology, Jinnah Postgraduate Medical Centre - Ahmad, Rizwana Malahat; Sher, Khalid; Devi, Lata; Abrar, Ateeba; Nisha, .; Muhammad, Fatima Ghulam (Biological and Clinical Sciences Research Journal, 2025)
Trigeminal neuralgia is a chronic pain condition characterized by recurrent episodes of severe facial pain. Carbamazepine is the first-line pharmacological treatment, but oxcarbazepine has emerged as a potential alternative with better tolerability and fewer side effects. Objective: To compare the efficacy of oxcarbazepine and carbamazepine in managing trigeminal neuralgia in patients presenting to the outpatient department of Neurology at Jinnah Postgraduate Medical Centre (JPMC), Karachi. Methods: This randomized controlled trial was conducted at Ward 28, Department of Neurology, JPMC, Karachi, from 21st September 2024 to 21st March 2025 after ethical approval from the institutional review board. A total of 122 patients aged 25–80 years of either gender with a clinical diagnosis of trigeminal neuralgia were enrolled using non-probability consecutive sampling. Patients with a history of surgical intervention for trigeminal neuralgia were excluded. Participants were randomly assigned to receive either oxcarbazepine or carbamazepine, and treatment efficacy was evaluated using the Visual Analogue Scale (VAS) for pain intensity. The primary endpoint was pain relief, and treatment response was categorized as good, moderate, or unresponsive. Results: Patients treated with oxcarbazepine demonstrated significantly greater pain relief than those on carbamazepine, as reflected by a lower mean VAS score (2.6 ± 1.2 vs. 3.7 ± 1.89, p = 0.001). Efficacy analysis revealed a good response in 69% of the oxcarbazepine group compared to only 20% in the carbamazepine group (p < 0.0001). Moreover, 66% of patients in the carbamazepine group remained unresponsive, whereas only 13% in the oxcarbazepine group showed no improvement. Conclusion: Oxcarbazepine is more effective and better tolerated than carbamazepine in managing trigeminal neuralgia, providing superior pain control and a more favorable response profile. These findings support oxcarbazepine as a preferable first-line treatment option in clinical practice.